PERFORMANCE OF AGRIBUSINESS AND SOCIO-ECONOMIC SYSTEMS OF SOYBEAN FARMERS IN NORTH SUMATRA - Leni Handayani; Bambang Hermanto; Dian Habibie; Sugiar Sugiar (Teunuleh Publisher, 2021)
Many factors must be considered in agricultural development in North Sumatra ranging from farmers as producers, availability of land for production, cultivation of planting, superior seeds, fertilizers, agricultural facilities/tools, infrastructure, post-harvest, distribution, processing of produce, price stability, to fulfilled food at the level of consumption. The purpose of this study is to analyze the performance of agribusiness systems as well as socio-economic factors of soybean farmers in North Sumatra. To assess the performance of agribusiness systems with good criteria, good enough and less good used questionnaire data by shifting the answer score by weight. To test socioeconomic factors, a formula for multiple linear regression is used. The results showed that farmers in carrying out aspects of organizing on average were good (score 31.6). Statistical tests of socio-economic factors of age (X2), education (X3), number of dependents (X5) have no real effect on the income of soybean farmers (Y) while land area (X1)and experience (X4) have a real effect on the income of soybean farmers (Y).